O-005 Mesenchymal stem cell-derived extracellular vesicles as a coiling adjunct to improve intracranial aneurysmal healing in a rabbit model. (23rd July 2022) - Belanger, B; Phelps, J; Bromley, A; Sen, A; Mitha, A
Abstract : Background: Although endovascular coiling has become a standard of care for treatment of intracranial aneurysms, up to 30% of treated aneurysms will recur. Using mesenchymal stem cells (MSCs) as an adjunctive therapy can potentially improve aneurysm healing, but the injection of cells may be impractical for routine use. Moreover, increasing evidence has found that the therapeutic effects of MSCs may be due to their release of a heterogeneous population of lipid membrane-bound nanoparticles called extracellular vesicles (EVs). Similar to MSCs, EVs can also localize to areas of inflammation, but have many advantages over a cell-based therapy including a better safety profile, reduced immunogenicity, and simplified production and storage. (Yuana et al., 2013, Bang&Kim 2019; Natasha et al., 2014, Gonzalez-Gonzalez et al., 2020) The purpose of this study, therefore, was to determine the effect of MSC-derived EVs in an in vivo aneurysm model. Methods: Aneurysms were created as previously described in two female New Zealand White rabbits (Belanger et al., 2021). Four weeks after creation, animals underwent digital subtraction angiography (DSA) to determine aneurysm size and patency. After the deployment of one to two framing coils in the aneurysm to stagnate flow, EVs from 6x10 7 adipose-derived MSCs were injected directly into the aneurysm sac using the same SL-10 catheter. Aneurysms were then coiled to completion with a goal packing density between 20% and 30%. Ninety days later, animals were sacrificed for histological processing and were compared to historical controls (Herting et al., 2019) in terms of aneurysm size, coil length per aneurysm, packing density, neointimal thickness, and histological healing score (Dai et al., 2006). Results: For the experimental group, aneurysm size, coil length per aneurysm volume, and packing density were 61.78 mm 3 ±22.11, 0.52 cm/mm 3 ±0.036, and 26.24%±1.75 while Herting et al. reported 119.3 mm 3 ±114.9, 0.417 cm/mm 3 ±0.18, and 24.3%±7.8, respectively (mean±SD). There was no significant differences in these metrics between the two groups (p=0.53, 0.76, 0.50, respectively (Student's T-test)). Comparison of neointimal thickness between the experimental group and historical controls was also not significantly different (0.03um±0.029 vs. 0.03um±0.01, p=0.99 (Student's T-test)), although histological healing score was significantly higher in the experimental group (11.5±2.12 vs. 4.5±2.4, p=0.02) ( figure 1 ). Conclusions: MSC-derived EVs as an adjunct to endovascular coiling may improve the histological healing scores of aneurysms, potentially reducing the risk of aneurysm recurrence after endovascular coiling. Additional studies are needed to more rigorously investigate this effect. Disclosures: B. Belanger: 1; C; NSERC Brain CREATE Program. J. Phelps: None. A. Bromley: None. A. Sen: 1; C; Natural Sciences and Engineering Research Council of Canada (NSERC), Office of the Vice President (Research), University of Calgary. A. Mitha: 1; C; Stryker Neurovascular, Fluid Biomedical. 2; C; Cerus Endovascular. 4; C; Fluid Biomedical.